Development Of High Performance Porcelain And Alumina Foam Structure For Porous Medium Burner - Jamaludin, Abdul Rashid (2016)
The requirements for better combustion process that emits low emissions can be achieved through porous medium burner (PMB). For that, the porous medium or porous inert media (PIM) installed inside PMB should have better properties. Therefore, the goal of this research is to fabricate PIM from porcelain (tri-axial compositions of kaolin clay, feldspar, and silica) and Al2O3 for PMB using a sponge replication technique (SRT). Inside the PMB, porcelain-PIM was installed as preheater zone, whilst Al2O3-PIM as combustion zone. The emphasized was given to Al2O3-PIM as it involved in combustion process. For the fabrication of PIM, natural (sago and tapioca starch) and synthetic poly(vinyl alcohol) (PVA) were used as the binder for slurry preparation. These binders were diluted and mixed with porcelain and Al2O3, respectively to form slurries. The slurries show pseudo-plastic behaviour, and was used for replication process using polyurethane (PU) sponge template. The replicated template was sintered at 1250 ºC and 1600 ºC, respectively to yield porcelain- and Al2O3-PIM substrates. The porosity of both substrates is within 79% to 90%. Porcelain- and Al2O3-PIM substrates with natural binders have bulky and finer surface morphology (skeleton strut), but defects (micropores and cracks) were evident compared to PVA added samples. During compressive test, the Al2O3-PIM substrate added with PVA destroyed in fragments, while sample contained natural binder collapsed steadily due to the existing defects. Subsequently, the Al2O3-PIM substrate was dip-coated with SiC-, Ni-, and Cr-based solutions (catalyst materials) and re-sintered at 900 °C, 1150 ºC, and 1250 ºC in vacuum atmosphere. A consolidated coating layer was observed at 1250 ºC, which contributed to reduction in micropores, cracks, and open cells. The porosity of dip-coated Al2O3-PIM also dropped significantly. Improvement in compressive strength (from 0.22 MPa to 0.78 MPa) and thermal conductivity (from 0.3446 W/mK 0.5476 W/mK) was observed for dip-coated samples. Finally, the dip-coated Al2O3-PIM was employed as combustion zone inside a prototype PMB. Combustion test was conducted at different fuel inlet. Comparison was made between the plain and dip-coated Al2O3-PIM. Plain Al2O3-PIM substrate shows maximum surface flame temperature of 634 ºC, whilst the temperature achieved by SiC-, Ni-, and Cr-coated Al2O3-PIM are 750 ºC, 741 ºC, and 739 ºC, respectively. The improved surface flame temperature for dip-coated samples have reduces CO (from 1300 ppm to 23 ppm) and COu emission (from 1190 ppm to 37 ppm). This signifies better combustion process due to the deposition of catalyst coating.